The Influence Of The Use Of Audio Visual And Multimedia Media And Learning Motivation On Learning Outcomes In Subjects Knowledge Of Textile Materials Class X - Chairunisa Wiji Hidayati; Atiqoh; Hari Karyono (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
This study aims to (1) To determine the effect of learning outcomes between the use of audio-visual media and multimedia multimedia in the subject of knowledge of textile materials. (2) To determine the effect of learning motivation with the use of audio-visual media and Multimedia in the subject of knowledge of textile materials. (3) To determine the effect of interaction on learning outcomes between the use of audio-visual media and Multimedia and learning motivation in the subject of knowledge of textile materials. This study used a quantitative approach with a quasi-experimental design. The data collection method for the independent variable uses a questionnaire, while for the learning outcome variable it uses a test or exam score document. To test the validity and reliability of the instrument, the Crunbach alpha formula was used. Meanwhile, to test the hypothesis using a statistical test using a two-way ANOVA with the help of SPSS. Based on the list of instrument tests, hypothesis tests and analytical tests, the instruments and data of this study have met the required statistical test requirements. The results of this study indicate that (1) the application of learning media using multimedia media has a better effect than using audio-visual media. (2) The application of learning media using multimedia media has an influence on learning motivation. (3) The interaction between the use of multimedia media in learning and learning motivation has a significant impact on student learning outcomes.